TEMPORAL TREND OF SUICIDE MORTALITY IN THE STATE OF PARAÍBA BETWEEN 2012 AND 2022: tendência temporal da mortalidade por suicidio no estado da Paraiba entre 2012 e 2022 - Matheus de Carvalho Pontes Silva; Vagna Cristina Leite da Silva Pereira; Adriane da Cunha Aragão Rios Fagundes; Cleyton Cézar Souto Silva (Revista de Ciências da Saúde Nova Esperança, 2025)
Suicide refers to the act of consciously ending one’s own life. This phenomenon, which persists over time, is a serious public health problem. Therefore, the aim of this study is to analyze the temporal trends in suicide mortality coefficients in the state of Paraíba, Brazil, between 2012 and 2022, by population subgroups, considering gender, age groups and race/color. To this end, public data sources were used, made available by the Department of Informatics of the Unified Health System (DATASUS), to extract suicide mortality data (X60.0 to X84.0), as well as data from the Brazilian Institute of Geography and Statistics (IBGE) for population estimates. Time trend analysis was carried out using the Prais-Winsten regression and the Annual Percent Change (APC) calculation to identify the percentage of annual variation over the period and classify the trends found. The trends in mortality coefficients in the different population subgroups were increasing over the period analyzed. The coefficients increased significantly, especially during the Covid-19 pandemic.